An An Analysis of The Relevance between The Content of The English Textbook “Headlines” for Grade XII and “Focal Point” by BSNP - Dwi Erna Finandiati; Rahayu Apriliaswati; Sumarni (JPTK : JURNAL PENELITIAN TINDAKAN KELAS, 2022)
The research is aimed to investigate the relevance between the focused materials in the English Textbook “Headlines” for grade XII and the criteria demanded by Focal Point. This research used qualitative research. This study used content analysis as the methodology. Based on the findings of analyzing the content of the textbook "Headlines" for XII grade of high school, it is found that the textbook content only fulfilled the 11 (eleven) points criteria of the focal point with a total of 31 points from A, B, and C of relevancy and it even did not reach half of the total. Therefore, it can be concluded that the textbook's content and related activities should be redesigned by following the criteria of Focal Point.